Mort et migration - Valérie Cuzol (Revue des Mondes Musulmans et de la Méditerranée)
Death and migration : Dealing with absence in the event of death.This article examines the trajectories of families disrupted by emigration. It attempts to explore the cost of absence through the example of the funeral practices of Maghrebin immigrant families. Loaded with intentionality and revealing of the individual’s attachments and personal memberships, one’s choice of burial site says much about who one is, here, there and now. Between disruption and continuity, family choices reflect an attempt to right any wrongs that may have been inflicted upon the collective sense of belonging by the act of migration, even though such compensation can never be fully satisfactory, whatever the choice of burial site. Absent for some, present for others, where should one bury one’s dead ? What is the meaning of absence when confronted by death ?